Radioisotope Excited X Ray Fluorescence Analysis of Ashes From Coal Power Plants of Turkey - Başsarı, A.; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Kluwer Academic Publishers, 1998)
Fifteen ash samples taken from filters and bottom products of boilers or chimneys of seven coal fired power plants in Turkey have been analysed quantitatively for some minor elements using radioisotope energy dispersive X-ray fluorescence (EDXRF). It is found that samples contain Cu, Zn, Rb, Sr, Zr, Mo, Cs, Sb, Ba, Pb, Y, La, Ce, Nd and Sm in different amounts. An ash sample taken from the electro-filter of the Ambarli, fuel oil fired-power plant was also analysed for comparison and found that it contained the smallest amount of potentially toxic elements.
Keywords: Physical Chemistry; Inorganic Chemistry; Power Plant; Turkey; Minor Element